1995
DOI: 10.3109/00365529509093306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild Malnutrition on Disaccharidase Activity and Glucose Uptake in Intestinal Brush Border Vesicles of Growing Monkeys

Abstract: This study indicates that even mild to moderate malnutrition decreases the digestion and absorption of carbohydrates throughout the small intestine, and it should not be ignored during the developing stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The causes of low serum concentrations of rifampicin may be various: poor quality of TB drugs (drug quality was ensured by the GDF in our study), HIV infection (although some studies did not observe differences between matched HIV-infected and uninfected TB patients), 6,18 -20 and wasting or malnutrition with associated hypoalbuminaemia, small-bowel oedema, villous atrophy and bacterial overgrowth leading to malabsorption. 21 The reduction of rifampicin plasma levels is a reason for concern due to the potential impact on treatment outcome and the development of rifamycin resistance. 13,22 We did not evaluate the association between rifampicin C max and clinical outcome because of our limited sample size, but the two patients who died had AUC and C max rifampicin values above the median value at both T0 and T1.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of low serum concentrations of rifampicin may be various: poor quality of TB drugs (drug quality was ensured by the GDF in our study), HIV infection (although some studies did not observe differences between matched HIV-infected and uninfected TB patients), 6,18 -20 and wasting or malnutrition with associated hypoalbuminaemia, small-bowel oedema, villous atrophy and bacterial overgrowth leading to malabsorption. 21 The reduction of rifampicin plasma levels is a reason for concern due to the potential impact on treatment outcome and the development of rifamycin resistance. 13,22 We did not evaluate the association between rifampicin C max and clinical outcome because of our limited sample size, but the two patients who died had AUC and C max rifampicin values above the median value at both T0 and T1.…”
Section: Discussionmentioning
confidence: 99%
“…Wastfor any of the compounds, and neither the variability in bioavailability (AUC) nor the variability in elimination (t 1/2 ) of isoniazid, ing or malnutrition sufficient to cause small-bowel edema, villous atrophy, or bacterial overgrowth might be expected to rifampin, and pyrazinamide was explained by interpatient differences in CD4 cell counts. result in malabsorption [34].…”
Section: Although Most Hiv-infected Patients With Tuberculosis (Tb)mentioning
confidence: 99%
“…Rana et al (8) demonstrated that severe malnutrition is related to decreased disaccharide activity and consequently affects digestion and absorption of disaccharides, especially lactose. It is probably connected with considerable protein deficiency.…”
Section: Original Article Wiecek Et Al Disaccharidases In Ibdmentioning
confidence: 99%
“…Elemental diet also shows immunological effects by increasing the supply of food and macromolecular antigens, changing intestinal bacterial flora, inhibiting intestinal loss of lymphocytes, and decreasing synthesis of inflammatory mediators. An adequate dietary regimen leads to improved protein and energetic balance, correction of micronutrient deficiency (vitamins, trace elements), and decreased intestinal loss of nutrients (6)(7)(8)(9).…”
Section: Malabsorption Of Carbohydrates Can Bementioning
confidence: 99%